THE STUDENTS’ MORPHOLOGICAL AWARENESS ON DERIVATIONAL MORPHEMES AND ITS RELATIONSHIP TO READING COMPREHENSION ON SEVENTH SEMESTER STUDENTS AT UNIVERSITY OF ISLAM MALANG - Siti Munawaoh (Jurnal Penelitian, Pendidikan, dan Pembelajaran, 2021)
Abstract: The aim of this research was to find out whether the students morphological awareness on derivational morpheme and its relationship to reading comprehension on seven semester students at University of Islam Malang. For population and sample the researcher target population of this study was seventh semester students who enrolled in English Department of Faculty of Teacher Training and Education at university level. The study is considered to take samples from large populations. It was made up of 60 students chosen using purposive-sampling technique. The instrument of this study was used Google form that has been speeded to object study via online messages. The result of this study the mean is in descriptive analysis morphological awareness and reading comprehension the mean of the morphological awareness scores for the participants is 75.63 and the mean of the reading comprehension scores for the participants is 74.55 from 60 students in seventh semester students at University of Islam Malang. The result Pearson Product Moment in SPSS is the correlation coefficient was .282, and the level of probability (p) significance (sig.2-tailed) was .029. It means that p (.029) was lower than .05. Thus, there is significant relationship between the students’ morphological awareness and their reading comprehension.Keywords: Morphological wareness, reading comprehension, relationship